Rosmarinus officinalis and Skin: Antioxidant Activity and Possible Therapeutical Role in Cutaneous Diseases - Federica Li Pomi; Vincenzo Papa; Francesco Borgia; Mario Vaccaro; Alessandro Allegra; Nicola Cicero; Sebastiano Gangemi (Antioxidants, 2023)
The rosemary plant, Rosmarinus officinalis L., one of the main members of the Lamiaceae family, is currently one of the most promising herbal medicines due to its pharmaceutical properties. This research aimed to evaluate the antioxidant role of Rosmarinus officinalis and its bioactive compounds on the skin, with a focus on the newly emerging molecular mechanisms involved, providing extensive scientific evidence of its anti-inflammatory, antimicrobial, wound-healing and anticancer activity in dermatological practice. The search was conducted on articles concerning in vitro and in vivo studies in both animals and humans. The results obtained confirm the antioxidant role of R. officinalis. This assumption derives the possibility of using R. officinalis or its bioactive elements for the treatment of inflammatory and infectious skin pathologies. However, although the use of rosemary in the treatment of skin diseases represents a fascinating line of research, future perspectives still require large and controlled clinical trials in order to definitively elucidate the real impact of this plant and its components in clinical practice.